2010
DOI: 10.1016/j.cell.2010.04.021
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP7 Is Not Required for B-RAF-Induced Melanocyte Senescence

Abstract: Induction of senescence permanently restricts cellular proliferation after oncogenic stimulation thereby acting as a potent barrier to tumor development. The relevant effector proteins may therefore be fundamental to cancer development. A recent study identified IGFBP7 as a secreted factor mediating melanocyte senescence induced by oncogenic B-RAF, which is found commonly in cutaneous nevi. In contrast to the previous report, we demonstrate that B-RAF signaling does not induce IGFBP7 expression, nor the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 47 publications
6
61
0
Order By: Relevance
“…IGFBP7 is a secreted protein recently proposed as a mediator of BRAF V600E -induced senescence in melanocytes (Wajapeyee et al 2008); this role, however, has been questioned by other authors (Scurr et al 2010). Interestingly, our recent results implicate IGFBP7 as a tumour suppressor protein in thyroid tumours: its expression is frequently lost in FTC and PTC, and its restoration modulates the transformed features of PTC-derived tumour cells (Vizioli et al 2010).…”
Section: G12vmentioning
confidence: 87%
See 1 more Smart Citation
“…IGFBP7 is a secreted protein recently proposed as a mediator of BRAF V600E -induced senescence in melanocytes (Wajapeyee et al 2008); this role, however, has been questioned by other authors (Scurr et al 2010). Interestingly, our recent results implicate IGFBP7 as a tumour suppressor protein in thyroid tumours: its expression is frequently lost in FTC and PTC, and its restoration modulates the transformed features of PTC-derived tumour cells (Vizioli et al 2010).…”
Section: G12vmentioning
confidence: 87%
“…INK4a and p21 CIP1 , two universally recognised OIS markers, and IGFBP7, a protein with an oncosuppressor role in thyroid tumours (Vizioli et al 2010), and often found involved in melanocyte OIS (Kortlever et al 2006, Acosta et al 2008, Kuilman et al 2008, Wajapeyee et al 2008, although its role in this process is controversial (Scurr et al 2010). Collectively, the three proteins were upregulated in PTMCs; the PTCs showed a variable pattern, including loss of expression; finally, the ATC sample was scored negative for the all proteins.…”
Section: Ink4amentioning
confidence: 93%
“…These findings have been confirmed by Bennett and coworkers (Gray-Schopfer et al 2006). Secreted IGFBP7 has been reported to play a central role in the initiation and maintenance of the senescent state of nevus cells (Wajapeyee et al 2008), but these findings were challenged recently Scurr et al 2010;Wajapeyee et al 2010).…”
Section: Ois In Models Of Nevus and Melanoma Formationmentioning
confidence: 99%
“…Nevertheless, a growing body of evidence supports the involvement of other pathways in the regulation of senescence, and in particular, in that of oncogene‐induced senescence (OIS) (Bianchi‐Smiraglia & Nikiforov, 2012; Christoffersen et al., 2010; Cipriano et al., 2011; Humbert et al., 2010; Lin et al., 2010; Scurr et al., 2010). …”
Section: Introductionmentioning
confidence: 99%